Squamous cell carcinoma of the pancreas: A systematic review and pooled survival analysis. (July 2017) - Ntanasis-Stathopoulos, Ioannis; Tsilimigras, Diamantis I.; Georgiadou, Despoina; Kanavidis, Prodromos; Riccioni, Olga; Salla, Charitini; Psaltopoulou, Theodora; Sergentanis, Theodoros N.
Abstract: The diagnosis and treatment of squamous cell carcinoma of the pancreas pose dilemmas in the clinical practice. The present study was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Eligible articles were sought in MEDLINE up to 30th April 2016. A pooled Cox regression analysis was performed to evaluate factors potentially associated with overall survival (OS) and relapse-free survival (RFS). Fifty-four cases of pure squamous cell pancreatic carcinomas were identified in total. The mean age was 61.9 years, and most patients were males (61.1%). The median OS was 7 months. Resectability (p = 0.003) and more recent publication year (p < 0.001) were associated with better OS, as was low/intermediate tumour grade (p = 0.032) with RFS. Despite its poor prognosis, survival rates of pancreatic squamous cell carcinoma seem improved during the recent years; resectability and low/intermediate grade emerged as favourable prognostic factors. Collaborative epidemiological studies are deemed necessary to further validate the results stemming from the published case reports of this rare entity. Highlights: Diagnosis and treatment of pancreatic squamous cell carcinoma (PSCC) is challenging. PSCC has a dismal prognosis with median survival of 7 months among reported cases. However, survival rates of PSCC seem improved during the recent years. Resectability and low/intermediate grade emerged as favourable prognostic factors. Collaborative epidemiological studies are rendered mandatory to reach firm results.